The passivation behavior of sputter-deposited W-xMo alloys on 0.5M NaCl solution - Bhattarai, Jagadeesh (Scientific World, 2012)
The passivation behavior of the sputter-deposited W-xMo alloys was studied in 0.5 M NaCl solution open to air at 25°C using immersion tests and electrochemical measurements. Corrosion rates of the W-xMo alloys containing less than 50 at% molybdenum content are in the range of 1.7-2.0 x10-2 mm/y and are slightly lower than that of tungsten metal whereas the corrosion rates of the alloys containing more than 50 at% molybdenum increased with the addition of molybdenum in the alloys. The W-83Mo alloy showed active-passive transition and transpassive dissolution. The open circuit potential of all the examined W-xMo alloys is shifted to noble direction with the addition of molybdenum content in the alloys. Scientific World, Vol. 10, No. 10, July 2012 p29-32 DOI: http://dx.doi.org/10.3126/sw.v10i10.6858